Analisis Prioritas Penanganan Ruas Jalan Strategis Untuk Pengembangan Wilayah di Kabupaten Demak - Natalia Eka Setya Krismawati (Department of Urban and Regional Planning, Diponegoro University, 2014)
The purpose of this study is to determine the priority handling strategic road in Demak, and to investigate the strategic road management applications that occur in the field of the development of the region in Demak. Primary data were obtained by questionnaire to 11 experts in the field of road handling. Data was collected through correspondence, and a list of questions (questionaire), the data analysis was performed by using the AHP Expert Choice program. A common form used in this study is the technique of Benefit-Cost Ratio Analysis (Benefit Cost Ratio), which is formed by two hierarchy is a hierarchy that is associated with Benefit Evaluation (KAD, PHD, and PWT), as well as associated with Evaluation Costs (BI, BOP also BPL). Based on the results of the assessment by questionnaire respondents, strategic road at Demak District such as Mranggen-Bulusari road, Karangawen-Pamongan road, Gajah-Dempet road Demak-Bonang road, and Bengkal-Karanganyar road. While the results of the analysis using the AHP method Expert Choice program found that the most important variable is KTBO for Criteria Benefits, then Costs for Criteria, the BOP is the most important variable. Then by comparing the results with the results of the Comprehensive Benefit Criteria with Criteria Comprehensive Cost obtained three (3) strategic roads which Benefit-Cost Ratio (Benefit-Cost Ratio) is greater than one (B/C>1), namely Mranggen-Bulusari road, Karangawen-Pamongan road, and Gajah-Dempet road. It can be concluded that according to the results of the above analysis, the existing field involving policy makers there is a difference, where Muka Kabupaten road, Menco-Jetak road, Gajah-Dempet road, Demak-Bonang road, and Trengguli-Demung road became a priority handling strategic road at 2013 by Demak Government. Meaning that there are still some things that are determined by certain parties that result from decisions made not entirely pure scientific approach structured results, and some are still subjective.